Geosmithia morbida sp. nov., a new phytopathogenic species living in symbiosis with the walnut twig beetle (Pityophthorus juglandis) on Juglans in USA - Kolarík, Miroslav; Freeland, Emily; Utley, Curtis; Tisserat, Ned (Mycologia, 2011)
Widespread morbidity and mortality of Juglans nigra has occurred in the western USA over the past decade. Tree mortality is the result of aggressive feeding by the walnut twig beetle (Pityophthorus juglandis) and subsequent canker development around beetle galleries caused by a filamentous ascomycete in genus Geosmithia (Ascomycota: Hypocreales). Thirty-seven Geosmithia strains collected from J. californica, J. hindsii, J. major and J. nigra in seven USA states (AZ, CA, CO, ID, OR, UT, WA) were compared with morphological and molecular methods (ITS rDNA sequences). Strains had common characteristics including yellowish conidia en masse, growth at 37 C and absence of growth on Czapek-Dox agar and belonged to a single species described here as G. morbida. Whereas Geosmithia are common saprobes associated with bark beetles attacking hardwoods and conifers worldwide, G. morbida is the first species documented as a plant pathogen.
Keywords: mezerníky ribozomální DNA; Spojené státy americké; DNA, Fungal; brouci; Plant Diseases; Animals; molekulární sekvence - údaje; DNA fungální; Hypocreales; Molecular Sequence Data; symbióza; Coleoptera; Symbiosis; Juglans; DNA, Ribosomal Spacer; zvířata; fylogeneze; nemoci rostlin; United States; Phylogeny